Possibility of using sweeteners in the prevention of obesity development - Wiktoria Staśkiewicz; Magdalena Wyleżoł; Agnieszka Bielaszka; Agata Kiciak; Marek Kardas (Kazimierz Wielki University, 2022)
Background. The problem of the 21st century both in Poland and around the world is overweight and obesity, and diabetes. Due to the increased incidence of these diseases, the consumption of intense sweeteners, which are used as substitutes for sucrose, has increased. The purpose of this study was to evaluate the sweet taste intensity of selected sweeteners in comparison with the benchmark - beet sugar. Methods. The material for the study consisted of four sweeteners: sugar, xylitol, stevia, and cane sugar. The substances were subjected to dilution in an infusion of black tea. This tea was then divided into 4 portions and each portion was sweetened with a different sweetener at a rate of 20g per 1l of infusion. The samples were coded with 3-digit codes, and the paired method was used for sensory evaluation. A total of 78 people participated in the study. Results. Differences in the intensity of sweet taste between beet sugar and the substitutes used were confirmed. Cane sugar and xylitol were characterized by a lower intensity of sweet taste, but these substitutes were preferred compared to beet sugar. Stevia is characterized by greater sweetness than beet sugar, while survey respondents strongly preferred beet sugar. Conclusions. Consumers, participating in the survey, prefer products with a less intensely sweet taste. Learning about consumers' preferences for sweet taste will allow the use of appropriately preferred substances in the production of food and dishes. This will have a positive effect on the sugar content of the daily ration and its overall consumption.